PERLINDUNGAN HUKUM TERHADAP SAKSI DAN PELAPOR DALAM MENGUNGKAP KASUS NARKOTIKA OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Khairani Miftahul Jannah; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Human life is inseparable from the problems to be faced and humans cannot avoid them.To overcome this we need a rule that can prevent and impose sanctions on people who do things that are not in accordance with applicable norms or ethics. One of the positive laws that exist in the community is the law governing the protection of witnesses and victims as stated in the state sheet which is the Republic of Indonesia Law No. 31 of 2014 concerning Protection of Witnesses and Victims. During this time many criminal cases have never been touched by the legal process to be tried because none of the witnesses or victims dared to reveal it, the threat of persecution, abduction of victims, witness or family members to murder is the main reason that makes them feel discouraged to be involved in giving testimony. From this background, the problem formulation was born namely, first how is the legal protection of witness and reporters in revealing narcotics crime by Pekanbaru City Police? Second, how is the effort to overcome barries to witness and reporter protection in revealing narcotics crime by Pekanbaru City Police? The purpose of this thesis is to find out the legal protection of witnesses and reporters in revealing narcotics criminal acts by the Pekanbaru City Police and know the effort to overcome the legal protection barriers to witnesses and reporters in revealing criminal acts by the Pekanbaru City Police.This type of research can be classified with research classified into sociological juridical research where the research examines the effectiveness of the law that is in force. From the research result, it is found that, first in protecting the rights of witnesses and victims, the government established an institution called the Witness and Victim Protection Agency (LPSK). Protection of witnesses and/or victims is declared to remain valid as long as it does not conflict with Article 44 of Law Number 13 year 2006 concerning protection of witnesses and victims. Second, the obstacles that occur are physical and psychological threats as well as criminalization efforts againts witnesses and victims or their families that make them afraid to give testimony before the court so that the most basic form of legal protection provide by law enforcement afficials and witness and victim protection agencies against Reporting criminal acts of narcotics abuse only conceal the identity of the reporter so it is not known by the perpetrators and also other syndicates.Keywords: Protection – Law – Witness – Reporter